Fertilizante organomineral para a produção de cana-de-açúcar - Sousa, Robson Thiago Xavier de (2014)
Fertilization of sugar cane plays an utmost important role in its entire production process directly influencing the productivity of the crop. The use of organomineral fertilizers as a source of nutrients may be an alternative to replace mineral fertilizers in this crop. The aim of this study was to verify the efficacy of the use of organomineral fertilizer on sugar cane. From 2011 to 2013 ten experiments were conducted under field conditions in the states of Minas Gerais, São Paulo and Goiás. In nine locations, doses of organomineral fertilizers were given according to the treatment with the mineral fertilizer recommended in each experimental area, following approximately 60, 80 and 100 % of the amount of N, P2O5 and K2O and a control treatment without applying fertilizers. In one local three doses of P2O5 by mineral and organomineral fertilizers were applied as well as a control treatment. The experimental design for all experiments was randomized blocks with five replications. During the crop cycle, assessment of plant height, leaf analysis (N, P and K), soil samples (before and after harvest of the experiments), yield, earnings were performed ships, technological variables and amount of sugar produced per hectare. Data were initially tested for assumptions of normality of residuals and homogeneity of variances. For yield analysis, the treatment means were compared using the Dunnet test at a significance level of 10%. The quantitative results were subjected to regression analysis and other variables were compared by Tukey test at 5% significance. There were no changes in nutritional levels of NPK in leaves even in treatments with lower dosage of NPK if treatments with organomineral fertilizer dosing with 60 % and 80 % of the NPK content is used in mineral fertilizer. The organomineral fertilizer was more efficient than the mineral fertilizer in both plant canes as for ratoon cane, being able to replace mineral fertilizers and submit by 24 % more efficiency in productivity from sugar cane. The application of this organomineral fertilizer provided greater profitability per hectare compared to mineral fertilizer.